Gender, migration and politics : pre- and post-migration experiences of Iranian women in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Politics, Massey University, Albany, New Zealand - Kooshesh, Parisa (Massey University, 2019)
Islam and Muslim women have become objects of considerable political controversy in countries such as Australia, France, and the USA, although less so in New Zealand. The dress-codes, customs and political allegiances of Muslim women are all debated for political reasons, and yet the diversity among these women is commonly overlooked. However, this study of women who have come to New Zealand from an orthodox Islamic regime shows quite different political orientations and issues in regards to migrant females from Muslim countries in the West. The main aims of this study are to examine the motivations of Iranian females to emigrate from Iran to New Zealand, and to investigate how they redefine their individual and social identities in the new country. The researcher involved semi-structured interviews with 34 Iranian females who migrated to New Zealand between 1979 and 2012. Their lived experiences (pre- and post-migration) are interpreted in the context of wider political ideologies, institutions, laws, social norms, and practices (of Iran and New Zealand) to show how political context influences what people can or cannot do in everyday life. In terms of the women’s motivations for migration, the study shows considerable variety. The participants’ stories reveal how the prevailing political ideology and gender-related policies of the Islamic Republic of Iran affected their daily lives, and how these policies influenced decisions to emigrate. These decisions are both ‘political acts’ and personal choices, involving personal aspirations as well as resistance to Iran’s political ideology and gender discrimination. In terms of post-migration experiences, this study illustrates how New Zealand’s social and political context has influenced the participants’ self-perceptions, their social roles as women, and the ways they relate to public institutions. The study also explores how these changes have affected power-relations within their families. Migration for Iranian females can involve a mixture of gains and losses to quality-of-life. Most commonly, however, these women find that adjusting to a new society and its more liberal, gender-equal environment means greater autonomy and agency. This study also investigates how participants redefine their post-migration social identities. The large majority of participants create a secular social identity after migration. They report being judged according to stereotypical expectations of Muslims, and they use diverse strategies to redefine who they are.
Tables 1 & 2 and Figure 1 have been removed for copyright reasons. Table 2 and Figure 1 may be accessed via the links provided in the References.
Keywords: Women; Iran; Social conditions; Sex discrimination against women; Iranians; New Zealand; Muslim women; Attitudes; Women immigrants; Emigration and immigration